SYMBOLISM IN THE NOVEL THE OLD MAN AND THE SEA WRITTEN BY ERNEST HEMINGWAY - WURIY HANDAYANI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2021)
This paper has intention to show the symbols hidden in the character of the novel The Old man and the sea. Furthermore, this paper has goal to find the connection between symbol and characters. The method uses in this research is qualitative research. The analysis involves characterization in this novel. It shows major and minor characters. Most of major character symbolizes something. Such as the old man symbolizes hero and the boy Manolin symbolizes purity. Not only the characters in this novel symbolize something but also the other elements in this novel symbolize something. For instance the sea symbolizes great nature and birds symbolizes friend. Studying the characters and symbol in this story offers more understanding to the readers.